(untitled) (KULT_online, 2015)
Wired Citizenship: Youth Learning and Activism in the Middle East, edited by Linda Herrera and Rehab Sakr, offers a rich collection of various studies focusing on young people’s online activities in virtual spaces in the Middle East and North Africa (MENA) region. Divided into two sections, the book investigates how the concepts and practices of democracy and citizenship are changing in the digital revolutionary age and how young people of a wired generation understand political and social change. Gathering together the works of social scientists from the fields of education policy, political science, sociology, anthropology, linguistics and international relations, this volume realizes an interdisciplinary and multidimensional picture of its subject matter.